Współpraca zagraniczna wrocławskich szkół wyższych jako element procesu integracji z Unią Europejską - Popiński, Krzysztof (International Cooperation of Wroclaw's Higher Schools as an Element of the European Integration Process - Overview, 2005)
The quantitative aspects of international cooperation of four biggest higher schools of education in Wroclaw have been analysed in the article. The schools are: the University, the Polytechnic, the Academy of Agriculture and the University of Economics Science. They constitute two-thirds of Wroclaw's potential as a scientific centre. Among other data, the analysis comprised the number of trips abroad, the number of visits by foreigners, the number of research programmes carried out in cooperation with foreign partners and the geography of those activities in the years 1989-2003, ie. in the transformation period, before Poland's membership in the E.U.As it turns out, at the end of 1980's and the beginning of 1990's a significant regress in that cooperation can be noticed. A revival of the schools' international contacts took place in the late 1990's. Before 2003 the number of trips abroad increased by 1/4, although the number of visits by foreigners was barely at the 1989 level. The number of scientific projects carried out with foreign cooperation hardly exceeded the 1980's level. The connections with the former socialist countries were particularly weak. Instead, contacts with the western scientific centres became more and more frequent. Steadily increasing scientific cooperation with centres situated in the E.U. has become the basis of international strategy of Wroclaw's higher schools. What is surprising is that the level of scientific exchange with the United States is marginal. On the other hand, contacts with the neighbours, especially Germany and the Czech Republic are worth noticing. It turns out that scientific liaisons with these and not other partners remain most important of all, at least in terms of the intensity of the exchange and the number of research topics and projects carried out jointly.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 467-477